The Ambivalence of the Scientific Ethos Is Irresistible - I. Т. Kasavin (Moscow Polytechnic University, 2021)
Ambivalence of the scientific ethos (R. Merton) today is still a topical issue under the escalation of contradictions between science and society. The autonomy of science, the solidarity of scientists in the face of internal and external challenges are the issues decisions of which are burdened by a number of antinomies such as "profession - vocation", "individual - collective" and "a priori - a posteriori". Is it possible to rid the ethics of science, designed to develop and represent moral norms for the scientific community, from this ambivalence? The article offers a sketch of the ethics of science, combining virtue epistemology with some ideas of J. Rawls and W. Pareto. It shows that the ethical assessment is irreparably present in the structure of roles and statuses in the scientific community, and epistemic virtues are intertwined with moral ones. In terms of this, ambivalence is a form of problematization inherent in any ethical discourse. Hence the task of the ethics of science is not to prescribe norms of behavior to a particular agent, but to explicate conditions of moral freedom.